Construction of a one-step multiplex real-time PCR assay for the detection of serogroups A, B, and E of Pasteurella multocida associated with bovine pasteurellosis - Wang, Haojie; Xin, Lingxiang; Wu, Yang; Liu, Yan; Yao, Wensheng; Zhang, He; Hu, Yunhao; Tong, Rendong; Zhu, Liangquan (Frontiers in Veterinary Science, 2023)
Bovine pasteurellosis, caused by serogroups A, B, and E of Pasteurella multocida (Pm), is mainly manifested as bovine respiratory disease (BRD) and hemorrhagic septicemia (HS). The disease has caused a great economic loss for the cattle industry globally. Therefore, identifying the Pm serogroups is critical for optimal diagnosis and subsequent clinical treatment and even epidemiological studies. In this study, a one-step multiplex real-time PCR assay was established. Three pairs of specific primers were prepared to detect the highly conserved genomic regions of serogroups A (HyaD), B (bcbD), and E (ecbJ) of Pm, respectively. The results depicted that the method had no cross-reaction with other bovine pathogens (Mannheimia hemolytica, Escherichia coli, Listeria monocytogenes, Staphylococcus aureus, Salmonella Dublin, Mycobacterium paratuberculosis, infectious bovine rhinotracheitis virus, and Mycoplasma bovis). The linear range (107 to 102 copies/μL) showed the R2 values for serogroups A, B, and E of Pm as 0.9975, 0.9964, and 0.996, respectively. The multiplex real-time PCR efficiency was 90.30%, 90.72%, and 90.57% for CartA, CartB, and CartE, respectively. The sensitivity result showed that the serogroups A, B, and E of Pm could be detected to be as low as 10 copies/μL. The repeatability result clarified that an intra-assay and an inter-assay coefficient of variation of serogroups A, B, and E of Pm was < 2%. For the clinical samples, the detection rate was higher than the OIE-recommended ordinary PCR. Overall, the established one-step multiplex real-time PCR assay may be a valuable tool for the rapid and early detection of the serogroups A, B, and E of Pm with high specificity and sensitivity.